Influence of recovery mode (passive vs. active) on time spent at maximal oxygen uptake during an intermittent session in young and endurance-trained athletes - Thevenet, D.; Tardieu-Berger, M.; Berthoin, S.; Prioux, J. (European Journal of Applied Physiology, 2007)
The aim of this study was to analyze the effects of recovery mode (active/passive) on time spent at high percentage of maximal oxygen uptake (VO2max),(VO2max) i.e. above 90% of VO2max (t90VO2max)VO2max(t90VO2max) and above 95% of VO2max (t95VO2max)VO2max(t95VO2max) during a single short intermittent session. Eight endurance-trained male adolescents (15.9 ± 1.4 years) performed three field tests until exhaustion: a graded test to determine their VO2maxVO2max (57.4 ± 6.1 ml min-1 kg-1), and maximal aerobic velocity (MAV; 17.9 ± 0.4 km h-1), and in a random order, two intermittent exercises consisting of repeated 30 s runs at 105% of MAV alternated with 30 s passive (IEP) or active recovery (IEA, 50% of MAV). Time to exhaustion (t lim) was significantly longer for IEP than for IEA (2145 ± 829 vs. 1072 ± 388 s, P < 0.01). No difference was found in t90VO2maxt90VO2max and t95VO2maxt95VO2max between IEP (548 ± 499-316 ± 360 s) and IEA (746 ± 417-459 ± 332 s). However, when expressed as a percentage of t lim, t90VO2maxt90VO2max and t95VO2maxt95VO2max were significantly longer (P < 0.001 and P < 0.05, respectively) during IEA (67.7 ± 19%-42.1 ± 27%) than during IEP (24.2 ± 19%-13.8 ± 15%). Our results demonstrated no influence of recovery mode on absolute t90VO2maxt90VO2max or t95VO2maxt95VO2max mean values despite significantly longer t lim values for IEP than for IEA. In conclusion, passive recovery allows a longer running time (t lim) for a similar time spent at a high percentage of VO2max.VO2max